Peristerophila nestoriae, a new species of quill mite of the family Syringophilidae (Acariformes: Prostigmata) parasitizing New Zealand Kaka Nestor meridionalis (Gmelin) (Psittaciformes: Strigopidae). Issue 4 (2nd October 2019) - Marciniak, Natalia; Skoracki, Maciej; Hromada, Martin
ABSTRACT: A new species of quill mite of the family Syringophilidae (Acariformes: Prostigmata), Peristerophila nestoriae sp. nov. from New Zealand Kaka, Nestor meridionalis (Gmelin) (Psittaciformes: Strigopidae) is described. This new species is morphologically similar to Peristerophila falcophila [Skoracki M, Hromada M, Kaszewska K, Unsoeld M. 2018. Peristerophila falcophila sp. nov., a new species and first record of quill mites (Acariformes: Syringophilidae) parasitizing birds of the order Falconiformes. Acta Parasitologica. 63:744–749. https://doi.org/10.1515/ap-2018-0088], and differs from it as follow: the stylophore is 130–140 long ( vs . 150–160 long); the propodonotal shield bear bases of setae ve, si, and c1 ( vs . only ve and si on the propodonotal shield); fan-like setae p′ and p″ of legs III and IV with 11–13 tines ( vs . 10 tines); the lengths of setae ag2 40–50 ( vs . 55–70). Our finding is the first record of the presence of syringophilid mite on host of the family Strigopidae and first report of the member of Peristerophila on psittaciform birds. So far, the syringophilids mites have not been found in New Zealand. LSID: urn:lsid:zoobank.org:pub:FB0C5B37-DF42-428C-8C81-8FA56EA67504